Лемма А. Картана по Б.Я. Левину с различными приложениями - Горин, Е.А. (Журнал математической физики, анализа, геометрии, 2007)
We give one of the delivered appeared while studing of Levin's lectures in Moscow in 1970. Also we give applications to some problems of the finited imensional and infinite-dimensional analysis. The peculiarity of our approach is: such parameters as that dimension do not appear in the initial estimates (at least explicitly). Generally, the article is a review, however some of the given results have not been published yet.